2024
DOI: 10.1039/d3sm01153d
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ions and humidity on charging of solid hydrophobic surfaces in slide electrification

Suhad Sbeih,
Aziz Lüleci,
Stefan Weber
et al.

Abstract: Water drops sliding down inclined hydrophobic, insulating surfaces spontaneously deposit electric charges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In this relative humidity range, the slide electrification measurements are not affected by the relative humidity. 53 …”
Section: Methodsmentioning
confidence: 99%
“…In this relative humidity range, the slide electrification measurements are not affected by the relative humidity. 53 …”
Section: Methodsmentioning
confidence: 99%
“…The surface charge and electrokinetic properties of liquids in contact with hydrophobic surfaces have been investigated extensively. However, the introduction of a gas phase appears to complicate the analysis and the contact charge transfer observed when a three-phase contact line moves over a fluoropolymer surface is not well understood. Several studies have revealed that the charge transfer may increase or decrease with ion concentration, , and this has recently been explained to be due to a combination of shear, which removes charge in the electrical double layer with quenching of the active sites near the fluoropolymer . However, it is not clear how other aqueous liquids miscible with water influence the quenching when hydration takes place near the interface.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, the acid−base model (proton donor−acceptor) was used to describe the charge separation in slide electrification, in which a PTFE surface interacts as a proton acceptor or donor. 11 In this context, the effect of pH 10,11,25 and various dissolved ions 11,15,21,25 on the droplet charge has been investigated. It has been proposed that the surface charge acquired by the sliding droplet and the ζ potential in the PTFE−water interface have the same physical basis.…”
Section: ■ Introductionmentioning
confidence: 99%